Pentingnya Perlindungan Merek Dalam Dunia Bisnis - Anik Tri Haryani (JURNAL DAYA-MAS, 2021)
Legal counseling aims to provide understanding and socialization to the public about the importance of brand protection in the business world. The brand is a sign that is attached to a item / service so that the goods / services are known by the community. Brands can also be used as promotional suggestions to consumers. But in reality there are still many small business actors who do not understand the importance of this brand. Therefore it is necessary to carry out counseling or socialization about the importance of the brand and how to register a brand. The method used is by approaching the community through counseling and socialization. Socialization was carried out in the village of Mojorayung, Wungu District, Madiun Regency, the village, there was a small and medium industrial. The Mojorayung village community is very enthusiastic with the counseling and they will be willing to provide brands to the goods they produce local government assistance.